Pengaruh Metode Drill Terhadap Keterampilan Teknik Dasar Passing Pada Siswa Ekstrakurikuler Sepak Bola SMA Negeri 1 Jasinga - Anwar Anwar; Evi Susianti; Saeful Ma’mun (Jurnal Ilmiah Wahana Pendidikan, 2022)
The purpose of this study was to determine the truth of the effect of the drill method on basic passing technique skills in soccer extracurricular students at SMA Negeri 1 Jasinga. This research is a quantitative research with pre-Experimental Design method with the type of Intact-Group Comparison. The population in this study amounted to 42 students who were registered to take part in extracurricular soccer activities. In this study using purposive random sampling technique, the sample used in this study amounted to 28 students, namely students who are still active and meet the terms and conditions. The instrument used in this research is a test. This test aims to measure the ability of basic passing technique skills in soccer extracurricular students of SMA Negeri 1 Jasinga. There are three stages in this study including pretest, treatment, and posttest. The data analysis technique used is quantitative descriptive analysis technique. The results of this study obtained the average value of the pretest group A and group B of 4.93 and for the average value of the posttest group A of 8.00 and group B of 8.14, which means there is an increase in the average results of the pretest and posttest for group A 3.07 and group B 3.21. The results of this study indicate that there is an effect of the drill method on students' basic passing technique skills, this can be proven by the results of hypothesis testing using the SPSS version 22 program, namely the value of Sig.(2tailed) from group A and group B <0.05, which is 0.000. So it can be concluded that there is an effect of the drill method on basic passing technique skills in soccer extracurricular students at SMA Negeri 1 Jasinga.